(untitled) (Revista Electrónica REDINE, 2018)
The review of the life and work of the Dr. Antonio Maria Pineda, it is a good moment to remember the greatness of the labor of the doctor, who has in his hands the hopes of a company that in him trusts his more valued good: that of his health. To think about his person and his facts; to learn of his virtues and of his dou bts, of his inventions, it is the best honoring that we can do to whom it took the love as principal features of his character for the land and the family, the longing for knowing and of culture, and the desire to collaborate to constructing a great Barquisimeto. The present work is structured of the following form: Antonio Maria Pineda, historical review, Hospital of the Charity, Hospital Antonio Maria Pineda, Bulletin of the Hospital of the Charity, his medical exercise, educational Pineda, Antonio Maria Pineda and the first university, civic and moral virtues, conclusions, recommendations